Beyond forest habitat qualities: Climate and tree characteristics as the major drivers of epiphytic macrolichen assemblages in temperate mountains. (29th January 2019) - Janssen, Philippe; Fuhr, Marc; Bouget, Christophe
Abstract: Questions: How are epiphytic macrolichen assemblages shaped by forest habitat quality as reflected by the availability of late‐developmental forest attributes (i.e., stand maturity) and the temporal continuity of the wooded state (i.e., forest continuity)? Are these two forest habitat features the main drivers of lichen assemblages, and if so, at which spatial scale? Study Site: Temperate mountain forests in the French Northern Alps. Methods: In our sampling design, we defined treatments by crossing forest continuity (ancient vs recent) and stand maturity (mature vs overmature), then quantified lichen response to the treatments at the stand ( n = 70) and tree scales ( n = 420). We distinguished between total macrolichen and Lobarion species alone. Finally, we assessed the influence of tree‐, stand‐ and landscape‐scale variables, as well as climatic variables. Results: Neither total macrolichen nor Lobarion diversity and composition were influenced by forest continuity, stand maturity or by stand‐ or landscape‐associated variables. Instead, climatic variables, light availability at the stand scale and host tree characteristics were the major drivers of lichen assemblages. In our mountain forests, this clearly shows that macrolichen were more influenced by local abiotic and biotic factors than by present or past human‐induced activities. Conclusions: Overall, we show that assemblage patterns in forest ecosystems may be driven by parameters that are not directly related to habitat quality. The influences of forest continuity and stand maturity on diversity and composition thus appear to be context‐dependent. In the ecological context of alpine forests, these findings highlight the benefits of selective‐cutting practices and illustrate the importance of structural heterogeneity, in terms of both improved accessibility to light and tree diameter diversity. Finally, the importance of temperature in shaping assemblage patterns suggests that global warming is probably the most significant threat to macrolichen conservation in temperate mountain forests. Abstract : Epiphytic macrolichen assemblages in temperate mountain forests were more influenced by local abiotic and biotic factors than by present or past human‐induced activities. Forest continuity and stand maturity factors, as well as stand‐ and landscape‐associated variables, were poor predictors of species richness and composition. Instead, temperature, light availability and host tree characteristics were the major drivers of lichen assemblages.